Development and evaluation of a mobile game to enhance the nutrition knowledge of elderly (Revista Brasileira de Ciências do Envelhecimento Humano, 2022)
The objective of this study was to develop and test a nutrition education methodology for the elderly using a mobile game. After being developed, the game installed on a tablet was used for three days by eleven elderly residents in the city of Palmeira das Missões, Brazil. The speech, expression, and application-handling difficulties of each elderly have been captured. They were interviewed to identify difficulties and the easy to use of the game and satisfaction and understanding about the nutrition education methodology. Some difficulties were recognized, but on average, 87.9% of the elderly indicated that the game is easy to use, 100% stated that icons and images are easy to recognize, 93.9% found the game fun, 100% indicated that it was able to generate clear knowledge about healthy eating. The game met the specificities of the target public and increased conceptual notions about nutrition and nutritional status in this population